Urban Guerrillas in the Irish War of Independence, 1919–1921 - Maciejewski, Michał (Tools of War, 2023)
The purpose of the following article is to present and analyse the tactical solutions employed by the Irish Republican Army and British forces in the Irish War of Independence in 1919–1921, particularly in the context of urban action. The article presents, the innovative methods of guerrilla warfare employed by the military wing of the Irish nationalist movement and the responses of British forces to these actions. The main issues covered in the text are: the Irish Republican Army's campaign against the Royal Irish Constabulary and the Dublin Metropolitan Police, the operation of the new British police units formed specifically to combat Irish separatism known as the Black and Brown and the Support Divisions, and the major combat operations carried out by the republican movement. In addition to analysing purely military operations, the article also describes the functioning of the intelligence services and the most important operations of the spy networks of both sides. In the context of Republican intelligence, the contribution of Michael Collins to the construction of an effective informant structure and the formation of a special liquidation group, the so-called Squadron, is particularly covered. From the perspective of the topic of the article, two specific moments in the Irish War of Independence were considered particularly significant. The first was the events of the so-called Bloody Sunday of November 1920 and the attack on the Customs House in Dublin on 25 May 1921. The article adopts a chronological structure, distinguishing three main phases of the conflict. The subject of the study was the testimony of the participants in the events described, found in the Bureau of Military History.